2019
DOI: 10.1007/s40265-019-01075-3
|View full text |Cite|
|
Sign up to set email alerts
|

Secukinumab: A Review in Ankylosing Spondylitis

Abstract: Secukinumab (Cosentyx®), a first-in-class fully human monoclonal antibody against interleukin-17A, is approved in several countries, including the USA and those of the EU, for the treatment of ankylosing spondylitis (AS). Subcutaneous secukinumab significantly improved the clinical signs and symptoms of AS versus placebo in three of four phase III trials. The benefits of secukinumab were generally seen regardless of whether patients had or had not received previous tumour necrosis factor (TNF) inhibitor therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 43 publications
1
53
0
1
Order By: Relevance
“…15 A few studies from real-life clinical practice, on a limited number of patients, confirmed the results of RCTs. 15 Secukinumab safety profile was satisfactory, with a slight increased risk for infections, 31 no increased risk of latent tuberculosis (TB) reactivation. 34 Due to the physiological protective role exerted by IL-17 on mucosae, 35 and on gut microbiome, 36 a special attention was reserved to the risk of opportunistic infections and increased occurrence of inflammatory bowel diseases induced by IL-17 inhibition.…”
Section: Licensed Anti-il-17 Biologics For the Treatment Of Asmentioning
confidence: 70%
See 3 more Smart Citations
“…15 A few studies from real-life clinical practice, on a limited number of patients, confirmed the results of RCTs. 15 Secukinumab safety profile was satisfactory, with a slight increased risk for infections, 31 no increased risk of latent tuberculosis (TB) reactivation. 34 Due to the physiological protective role exerted by IL-17 on mucosae, 35 and on gut microbiome, 36 a special attention was reserved to the risk of opportunistic infections and increased occurrence of inflammatory bowel diseases induced by IL-17 inhibition.…”
Section: Licensed Anti-il-17 Biologics For the Treatment Of Asmentioning
confidence: 70%
“…33 The efficacy of secukinumab in AS at the dose of 150 mg/sc/was demonstrated in 5 RCTs of MEASURE program. 15 Overall, the drug significantly reduced the disease activity, improved the quality of life, with slowing down of the structural damage both in naïve and anti-TNF refractory AS patients. 15 A few studies from real-life clinical practice, on a limited number of patients, confirmed the results of RCTs.…”
Section: Licensed Anti-il-17 Biologics For the Treatment Of Asmentioning
confidence: 93%
See 2 more Smart Citations
“…The newer agent, IL17-A inhibitor, has proved to be useful for (a) TNF inhibitor-naive patients with active AS, and also for (b) those who have a poor response to (or, are intolerant) to TNF inhibitors. [ 5 ]…”
mentioning
confidence: 99%